Educar en tiempos extraordinarios: dirigir instituciones educativas en pospandemia, un estudio cualitativo en escuelas de México (Investigaciones) - Ortega Barba, Claudia Fabiola (2023)
The relevance of managerial action within the school system became evident in the crisis caused by COVID-19. The purpose of this research is to show the experiences experienced by managers to meet the needs caused by the crisis. To achieve this, the qualitative and comparative approach was used, integrating the principles of symbolic interactionism, using focus groups as a technique for collecting information and, for its analysis, the inference ladder method. It is concluded that the impact on schools was different and diverse in each due to different conditions. Thus, the strategies undertaken by managers responded to their own reality. Conventional institutions found it more difficult to deal with the crisis, while versatile organizations were able to adapt to the new remote learning ecosystem more effectively.